2014
DOI: 10.3389/fnagi.2014.00208
|View full text |Cite
|
Sign up to set email alerts
|

The Neuromuscular Junction: Aging at the Crossroad between Nerves and Muscle

Abstract: Aging is associated with a progressive loss of muscle mass and strength and a decline in neurophysiological functions. Age-related neuromuscular junction (NMJ) plays a key role in musculoskeletal impairment that occurs with aging. However, whether changes in the NMJ precede or follow the decline of muscle mass and strength remains unresolved. Many factors such as mitochondrial dysfunction, oxidative stress, inflammation, changes in the innervation of muscle fibers, and mechanical properties of the motor units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
237
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(250 citation statements)
references
References 148 publications
6
237
0
7
Order By: Relevance
“…Such a reversal in neuromuscular function with RT was demonstrated by two studies: a 4% rise in MVC relative to an electrically stimulated maximum in healthy elderly33 and improvement in skeletal muscle innervation reported in obese older adults 40. The neuromuscular junction (NMJ) is the interface between the muscle and nervous system; it is known to be disrupted by oxidative stress, leading to degeneration and denervation with age 41. Reduction of oxidative stress has been shown to improve the NMJ and specific force in mouse studies 42.…”
Section: Discussionmentioning
confidence: 96%
“…Such a reversal in neuromuscular function with RT was demonstrated by two studies: a 4% rise in MVC relative to an electrically stimulated maximum in healthy elderly33 and improvement in skeletal muscle innervation reported in obese older adults 40. The neuromuscular junction (NMJ) is the interface between the muscle and nervous system; it is known to be disrupted by oxidative stress, leading to degeneration and denervation with age 41. Reduction of oxidative stress has been shown to improve the NMJ and specific force in mouse studies 42.…”
Section: Discussionmentioning
confidence: 96%
“…For example, poor handgrip strength among healthy middle‐aged subjects was found to significantly predict functional limitations and disability 25 years later (Rantanen et al ., 1999). The biology that drives muscle strength decline is complex, with hormonal changes, inflammatory pathway activation, mitochondrial physiology, malnutrition, and exercise all likely playing a role (Walston, 2012; Gonzalez‐Freire et al ., 2014). Further identification of biologically relevant pathways that influence muscle strength maintenance and decline could be important in the development of future treatment or prevention strategies.…”
Section: Introductionmentioning
confidence: 99%
“…46 Even though the pathogenesis of neuromuscular junction impairment is still poorly understood, many factors seem to be primarily involved, such as mitochondrial alteration, age-related chronic inflammation, and neurodegeneration. 26 Previous studies demonstrated an age-related remodeling of motor units leading to progressive denervation, followed by reinnervation from remaining adjacent neurons 18 ; this aspect seems to be involved in the age-related loss of muscle strength and force-producing capacity. 19,47 Denervation of skeletal muscle results in atrophic angular fibers scattered at random or in small or large groups within a biopsy; adjacent intact motor nerve may sprout and reinnervate clusters of denervated fibers resulting in fiber-type grouping.…”
Section: Discussionmentioning
confidence: 99%
“…12,43,44,45 At present, sarcopenia has been defined as the condition of muscle wasting strictly linked to aging, characterized by loss of skeletal muscle mass and function, which may affect both animals and humans, at different stages of severity 12,27,43 ; it is characterized by gradual loss of skeletal muscle mass resulting in decline of muscle function characterized by a decline in force-producing capacity and maximum velocity of shortening of muscle fibers. 48 These age-related alterations in skeletal muscle are attributed to a complex of factors involving neuromuscular junction, 26 muscle structure (architecture and fiber composition), and metabolism. 43,47,49 The loss of muscle mass and strength results from the progressive atrophy and loss of single muscle fibers, 23 along with loss of both types of motor units (slow and fast).…”
mentioning
confidence: 99%